perilaku produsen dalam pemenuhan kewajiban sertifikat halal pada produk olahan tempe di UD. muncul jaya perspektif etika bisnis islam - Erlin, Ahmad Fahmi Rusdi Baihaqi (Irtifaq, 2025)
This study examines the behavior of producers in fulfilling the obligation of halal certification for processed tempeh products at UD. Muncul Jaya from the perspective of Islamic business ethics. Using an empirical juridical method, the research explores the producer’s traditional background and their transition toward compliance with legal and sharia principles. The findings show that UD. Muncul Jaya has made efforts to uphold the principles of trustworthiness (amanah), honesty (ṣidq), halalan thayyiban, and to avoid deception (tadlīs) and uncertainty (gharar). Although halal certification was only pursued after decades of operation, the producer has shown a positive transformation through increased halal literacy and commitment to ethical Islamic values in business. Keyword: Islamic business ethics, MSMEs, halal production, tempeh industry, Kalisari Village